Application of DCIM to MPIE-MoM analysis of 3D PEC objects in multilayered media. - Yaxun Liu (IEEE Transactions on antennas and propagation)
The Formulation-C Green's functions for multilayered media are reformulated in this paper to extract z-dependent part when the source and observation points are in different layers. The discrete complex image method (DCIM), is applied to obtain complex images independent on z but dependent on z´. For simulation of three-dimensional (3-D) perfectly electrical conduction (PEC) objects penetrating two or more layers, tables of complex images are built in a z´-grid. During the matrix-filling stage of the mixed-potential integral equation, together with method of moments (MPIE-MoM), the spatial-domain Green's functions are interpolated from values in the z´-grid, while these values are calculated from complex images in the z´-grid. This interpolation scheme is more efficient than those directly storing the spatial-domain Green's functions. Numerical examples are given for analyzing a dipole in a two-layered media